(untitled) (Research, Society and Development, 2021)
Objectives: This paper aims to analyse current data in the literature about the clinical manifestations of COVID-19 in ophthalmology, the duration of the symptoms, and correlate them with the systemic manifestations. Methods: It is a narrative literature review, using the following search terms: coronavirus infection, betacoronavirus, COVID-19, ocular disease, and ocular manifestation, using the electronic databases LILACS and MEDLINE, searching for articles published between May to August 2020. Results: The initial search identified 824 articles and 14 attended the inclusion criteria. Of the reported cases of keratoconjunctivitis, the most described ocular manifestations are conjunctival hyperemia, monocular and binocular, and eyelid edema. Other symptoms that can appear frequently are diplopia and binocular diplopia; foreign body sensation, blurred vision, and presence of watery and viscous secretion. Conclusion: In conclusion, the main ocular manifestation associated with the presence of SARS-CoV-2 is conjunctival hyperemia, with a variable duration between 2 and 30 days.